Academic Honesty among Students of Selected Dental Colleges of Bangladesh (Bangladesh Journal of Medical Education, 2019)
Objectives: The purpose of this research is to explore some of the issues related to academic honesty among students in Dental colleges, the challenges faced by them to do well academically in an honest manner.Methods: This cross sectional study was conducted at ten public and private dental colleges of Bangladesh. The students were asked to fill up a self-administered, semi structured questionnaire containing about their Academic honesty and behavior. Data was collected using convenience sampling method. Sample size was 739.Results: The study revealed 30% marked proxy for their friends and 28.9% asked their friends to mark proxy for them.10.8% cheated in examination using notes. Also 38.7% copied answers from another student during an examination.Conclusion: The study revealed that a large number of dental students admitted to cheating and involvement in other forms of academic dishonesty.Bangladesh Journal of Medical Education Vol.10(1) 2019: 6-13